IMPLEMENTATION OF STAD COOPERATIVE LEARNING TO IMPROVE STUDENTS’ SELF-ESTEEM TOWARD MATHEMATICS LEARNING - Arsyil Waritsman; Nidya Nina Ichiana; Neni Iryani (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This study is aimed to improve students’ self-esteem toward mathematics learning in MTs Ummul Quro through Students Team Achievement Divisions (STAD) cooperative learning. This was a classroom action research study and the research subjects were thirty one students of Grade IX B. The data as indicators of the success of class actions were collected using a self-esteem questionnaire for mathematics learning, mathematics achievement tests, and observation sheets for the implementation of STAD cooperative learning. In the implementation, the results showed that in Cycle I there were still students who had low self-esteem, 67.74% of students attained KKM (short for kriteria ketuntasan minimal or ‘the criterion for minimum mastery’), and the percentage of the implementation of STAD cooperative learning was 85.33%. In Cycle II, no students had low self-esteem, 77.42% of students attained KKM, and the percentage of the implementation of STAD cooperative learning was 96.67%. In general, the results of the study showed that STAD cooperative learning could improve the self-esteem of Grade IX B of MTs through two cycles